The Src Kinase Lck Facilitates Assembly of HIV-1 at the Plasma Membrane - Strasner, Amy B. (2008)
HIV-1 assembly and egress are driven by the viral protein Gag and occur at the plasma membrane in T cells. Recent evidence indicates that secretory vesicles and machinery are essential components of virus packaging in both T cells and macrophages. However, the pathways and cellular mediators of Gag targeting to the plasma membrane are not well characterized. Lck, a lymphoid specific Src kinase critical for T cell activation, is found in the plasma membrane as well as various intracellular compartments and it has been suggested to influence HIV-1 replication. To investigate Lck as a potential regulator of Gag targeting, we assessed HIV-1 replication and Gag induced virus-like particle release in the presence and absence of Lck. Release of HIV-1 and virus like particles was reduced in the absence of Lck. This decrease in replication was not due to altered HIV-1 infection, transcription or protein translation. However, in T cells lacking Lck, HIV-1 accumulated intracellularly. In addition, expressing Lck in HeLa cells promoted HIV-1 Gag plasma membrane localization. Palmitoylation of the Lck unique domain, which is essential for directing Lck to the plasma membrane, was critical for its effect on HIV-1 replication. Furthermore, HIV-1 Gag directly interacted with the Lck unique domain in the context of infected cells. These results indicate that Lck plays a key role in targeting HIV-1 Gag to the plasma membrane in T cells.